2018
DOI: 10.3390/nano8090727
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as a Solution for Eliminating the Risk of Mycotoxins

Abstract: Mycotoxins are toxic secondary metabolites produced by certain filamentous fungi. The occurrence of mycotoxins in food and feed causes negative health impacts on both humans and animals. Clay binders, yeast cell walls, or antioxidant additives are the most widely used products for mycotoxin elimination to reduce their impact. Although conventional methods are constantly improving, current research trends are looking for innovative solutions. Nanotechnology approaches seem to be a promising, effective, and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 175 publications
(145 reference statements)
2
79
0
1
Order By: Relevance
“…In an attempt to mitigate the risk of mycotoxin contamination in food and feed, different pre-and post-harvest physical (e.g., crop rotation, thermal treatment, and irradiation), chemical (e.g., acids/bases and absorbents), and biological (e.g., microbial and enzymatic degradation) strategies have been deployed [27,[204][205][206][207]. Besides these conventional mitigation methods, nanotechnology may be an innovative solution to mycotoxin contamination [208]. It is not possible in this review to discuss all the approaches; instead, the discussion will focus on remediation strategies that are most widely used in the animal feed industry, especially the use of mycotoxin adsorbents as feed additives.…”
Section: Strategies To Counteract Mycotoxin Contaminationmentioning
confidence: 99%
“…In an attempt to mitigate the risk of mycotoxin contamination in food and feed, different pre-and post-harvest physical (e.g., crop rotation, thermal treatment, and irradiation), chemical (e.g., acids/bases and absorbents), and biological (e.g., microbial and enzymatic degradation) strategies have been deployed [27,[204][205][206][207]. Besides these conventional mitigation methods, nanotechnology may be an innovative solution to mycotoxin contamination [208]. It is not possible in this review to discuss all the approaches; instead, the discussion will focus on remediation strategies that are most widely used in the animal feed industry, especially the use of mycotoxin adsorbents as feed additives.…”
Section: Strategies To Counteract Mycotoxin Contaminationmentioning
confidence: 99%
“…It has been reported that selenium (Se) application decreases Cd uptake [75]. In similar studies, selenium, copper, zinc oxide and many other metallic nanoparticles [92][93][94][95][96][97][98] have been studied in food processing, packaging and preservation against phytopathogens and rodents. The washing with water or soaking in solutions of salt and some chemicals e.g.…”
Section: Recommendationsmentioning
confidence: 99%
“…Mycotoxins are toxic secondary metabolites produced by several mold fungi, whose occurrence in food and feed cause deleterious health effects on humans and poultry. Yeast cell walls, clay binders, and antioxidant additives are the most widely used products to eliminate mycotoxin and to reduce their harmful effect (Horky et al, 2018). B. cinerea culture filtrates may induce toxic effects when applied to plant tissue (Elad, 2004).…”
Section: Mycotoxinsmentioning
confidence: 99%